Feasibility and Benefits of Establishing a Corporate University in the Home Healthcare Industry - Tulsiani, Ravinder (Digital Repository of Theses, 2025)
The home healthcare industry is at a transformative stage, in which there is an ever-growing demand for services, yet such an urgent need for capable professionals exists. Some key challenges this sector faces include a need for more skilled professionals and the specialized nature of training necessary for home health care. The study explores if forming a corporate university would be feasible and beneficial as a strategic solution to these challenges, focusing on SE Health as the home healthcare leader. This study adopts a mixed-methods design, which quantitatively surveys and qualitatively interviews various stakeholders in SE Health to obtain comprehensive data. It sought to ascertain how well a corporate university would serve in pursuit of aligning employee development with organizational objectives, improving professional competencies, and creating a culture of continuous learning. This paper explores the multifaceted nature of corporate universities in realizing a new suite of skills, standardization of training, and revolutionizing standards of patient care. The findings indicate that corporate universities can play a crucial role in addressing the training gap for home health through continuous, adaptive learning applied to the specific needs of home health professionals. The study also found that organizational culture plays a vital role in successfully implementing and accepting a corporate university. This demonstrates how SE Health proactively positioned an educational institution within its strategic framework to meet significant organizational goals and industry standards. The expected outcome of this research will contribute to a critical discussion of training and development in the healthcare sector. Research shows how corporate universities could be transformational, opening new avenues to reimagine home health workforce development in the future. The findings from this research will have practical implications for SE Health and for the model to be adapted to an organization interested in better training and development.